2017
DOI: 10.1016/j.jbo.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of predictors of bone metastasis in colorectal cancer patients

Abstract: BackgroundWe explored risk factors for bone metastasis (BMs) in colorectal cancer (CRC) to improve in early diagnosis and follow-up and to reduce bone metastasis.MethodsWith a retrospective analysis of 2066 patients with CRC treated in our institution from January 2006 to January 2015, we assessed high-risk variables associated with bone metastasis using univariate and multivariate analyses.ResultsOf those subjects studied, 102 patients developed BMs, including 62 of 1014 the rectal cancer patients and 40 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 19 publications
4
31
2
Order By: Relevance
“…In previous study, Liu et al [ 21 ] revealed that a high CEA level in CRC patients with BM was prone to a poor prognosis. And Zhenghong et al [ 4 ] suggested that elevated CEA was also one of the risk factors for predicting BM in patients with CRC, which was consistent with our results. As a risk factor for diagnosing BM in CRC, the accuracy of it was good (AUC = 0.791), and the sensitivity and specificity were 81.1% and 70.6%, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In previous study, Liu et al [ 21 ] revealed that a high CEA level in CRC patients with BM was prone to a poor prognosis. And Zhenghong et al [ 4 ] suggested that elevated CEA was also one of the risk factors for predicting BM in patients with CRC, which was consistent with our results. As a risk factor for diagnosing BM in CRC, the accuracy of it was good (AUC = 0.791), and the sensitivity and specificity were 81.1% and 70.6%, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…In previous studies, the tumor location was detected to be an independent risk factor for predicting BM in CRC. [ 4 , 17 ] But this result was not confirmed in our study.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…In CRC, bone metastases usually develop later than those in other organs or tissue, such as liver and lung metastases, and there is a preferential link between bone and lung metastases. The prognosis is more severe in cases in which the metastasis of the tumor involves several sites simultaneously [22]. Bone metastases, perhaps more than others, are highly debilitating because of the various bone-related clinical pictures that they entail.…”
Section: Crc and Bone Metastasesmentioning
confidence: 99%
“…Studies on this topic were performed by evaluating cases of rectal or colon cancer cases individually. Recently, Zhenghong et al [22] have reported a higher percentage of bone metastases in rectal cancer patients than in CRC patients. Probably, this finding may depend on the broader vascularization in the rectum compared to the colon [23,24].…”
Section: Crc and Bone Metastasesmentioning
confidence: 99%